Science, faith and the climate crisis - Myers, Sally; Hemstock, Sarah; Hanna, Edward (Emerald points., 2020)
Inspired by a 2019 conference, Moana Water of Life, and including real-life insights from a diverse range of participants, this book showcases the potential fruits of open dialogue between stakeholders to navigate the critical challenges to planetary health caused by the climate crisis.